PENYALURAN DANA PIHAK KETIGA DAN SUKU BUNGA SEBAGAI VARIABEL MODERASI TERHADAP PROFITABILITAS BANK - John William (STIE Perbanas Surabaya, 2012)
Indonesian Bankings profit growth during the year 2004-2009 had been constantly fluctuating with a down tendency each year, but the amount of deposits and total assets always went up. This anomaly can be influenced by the factors, some of which were used as variables in this study. This study uses secondary data from banks financial reports such as BI rate and Blanket Guarantee Rate, during the first quarter of 2006 to the fourth quarter 2009. The purposive sampling was employed by ranking the criteria based on the largest number of diposits and total assets with a share of at least 5% of all commercial banks in Indonesia. The analysis was done by performing mathematical calculations and statistics from various financial ratios that reflect the growth rate of deposits products and their distribution within the reference rate. It was found that only two variables can significantly affect the banks NIM ratio, deposits and moderation of saving. Another results showed that moderation of savings become the most dominant variable.